Mycoplasma iowae infection in young Turkeys - Bradbury, Janet M.; Ideris, Aini; OO, Tin Tun (Taylor and Francis Group, 1988)
A comparison was made of the effect of five different strains of M. iowae after inoculation of one-day-old poults via the thoracic air sac and foot pad. Three strains appeared to be more virulent and more invasive than the other two, causing stunting, poor feathering and leg abnormalities including chondrodystrophy. One of these three strains was used in a second experiment in which three routes of infection were compared. Infection in ovo caused a severe generalised disease in hatched poults with high mortality. The only two birds which survived into the third week developed chondrodystrophy. One group was infected orally at one day of age and some birds developed bone and joint abnormalities but another group, infected via both the thoracic air sac and the foot pad, also at one day of age, developed a higher incidence of these abnormalities, which included chondrodystrophy, rotated tibia, deviated toes and, in a few cases, erosion of the articular cartilage of the hock joint. Some of the control uninfected birds developed leg abnormalities but never chondrodystrophy, rotated tibia or cartilage erosion. M. iowae was most widely disseminated in tissues following in ovo infection and least after oral infection. Isolations became less frequent with age and no organisms were recovered in birds sampled at 12 weeks. In neither experiment could antibodies to M. iowae be detected by rapid agglutination.